ANALISIS KELAYAKAN ASPEK NON FINANSIAL USAHATANI MERICA (Piper nigrum L.) DI DESA TANETE KECAMATAN MAIWA KABUPATEN ENREKANG - Halimah, Andi Sitti; Nuddin, Andi (Universitas Negeri Makassar, 2018)
Pepper is a commodity which has a potential to be developed because it is an important commodity. The farming of pepper is necessary high investments so that it needs a feasibility study of the pepper of farmer’s level. The study aims to to determine feasibility of pepper farming in Tanete Village, based on nonfinancial aspect such as market aspect, technical aspect, management aspect, and also social, economic, and environmental aspect. Methods of analysis data which are used on this research is qualitative. The research result showed that the pepper farming in Tanete Village, Maiwa Subdistrict-Enrekang District is feasible to be done .